Effects of ultrasonic rotating extrusion assisted wire arc additive manufacturing on the microstructure and mechanical properties of 5356 aluminum alloy - Rongtao Zhu; Liang Zhang; Longhan Duan; Zhaofeng Liang; Chuang Li; Bo Yuan; Peng Du; Zhiwen Xie; Yaping Zhang (Ultrasonics Sonochemistry)
Wire Arc Additive Manufacturing (WAAM) for the fabrication of lightweight Al alloy represents a burgeoning area of research. Despite this, the presence of porosity defects, coarse surface grain sizes, and the clustering of precipitated phases in WAAM-produced Al alloy samples have been identified as detrimental to their mechanical properties, rendering them inadequate for contemporary service requirements. In this investigation, an innovative approach termed Ultrasonic-Rotating Extrusion-Wire Arc Additive Manufacturing (U-RE-WAAM) was proposed, which integrates the synergistic effects of ultrasonic and mechanical force fields into the WAAM process. Comparative analysis were conducted on defects, microstructure and mechanical properties between WAAM and U-RE-WAAM samples to investigate the impact of U-RE-WAAM on aluminum alloy samples. The results show that the mechanical force field causes a large amount of plastic deformation, which refines the grain size and restructures the precipitation phase from clustered aggregates to a fine dispersion. Furthermore, the U-RE-WAAM process achieves a reduction in porosity and an enhancement in grain size and precipitated phase distribution by the coupling of mechanical force field and ultrasonic energy field. Consequently, the mechanical properties of U-RE-WAAM samples are markedly superior, with a 32.8% increase in hardness and significant improvements in yield strength 81%, ultimate tensile strength 41%, and elongation 38.9%.